Dengue activates mTORC2 signaling to counteract apoptosis and maximize viral replication - Carter, Christoph C.; Mast, Fred D.; Olivier, Jean Paul; Bourgeois, Natasha M.; Kaushansky, Alexis; Aitchison, John D. (Frontiers in Cellular and Infection Microbiology, 2022)
The mechanistic target of rapamycin (mTOR) functions in two distinct complexes: mTORC1, and mTORC2. mTORC1 has been implicated in the pathogenesis of flaviviruses including dengue, where it contributes to the establishment of a pro-viral autophagic state. Activation of mTORC2 occurs upon infection with some viruses, but its functional role in viral pathogenesis remains poorly understood. In this study, we explore the consequences of a physical protein-protein interaction between dengue non-structural protein 5 (NS5) and host cell mTOR proteins during infection. Using shRNA to differentially target mTORC1 and mTORC2 complexes, we show that mTORC2 is required for optimal dengue replication. Furthermore, we show that mTORC2 is activated during viral replication, and that mTORC2 counteracts virus-induced apoptosis, promoting the survival of infected cells. This work reveals a novel mechanism by which the dengue flavivirus can promote cell survival to maximize viral replication.